Juwayni's ta'wil understanding in the fiqh usul tradition - Buğda, Sadrettin (ATATURK UNIV, FAC THEOLOGY, 2021)
Scholars have set some kaidahs and principles in order to prevent the mistakes that may occur in commenting of the na and to ensure interpretation of the na in compliance with the divine will. Accordingly, scholars have made an effort to determine the scope and limits of the activity of ta'wil, which is the act of revealing the hidden meanings in the na through dalils(evidence). One of these scholars is Imam al-Haramayn al Juwayni (478/1085). He determined the general framework of ta'wil in the category of words in and revealed the existence of ta'wil through examples. Since all words were not suitable for ta'wil, he categorized them in terms of their suitability with ta'wil. While some usulists say that ta'wil can be practiced on the words described as na, Al-Juwayni states ta'wil is out of question in na. Likewise, he states ta'wil cannot be made on mujmal, mufassar and mushtarak words which are difficult to understand. Al-Juwayni emphasizes that ta'wil can only be practiced on words that are zahir(clear) in meaning. While he absolutely approves ta'wil from usulistic aspect; he reflects two different views on kalam issues. In this study, besides Al- Juwayni's usul works, by taking his works on kalam as the base, it is aimed to reveal his understanding of improvement. Extended Summary It is not possible to say that alkalam alalhi is at the same level in terms of kalima-maenaa (wordmeaning) relation. While maenaa intended to be expressed from some kalima of the `iilhi khitab, it is clear in a way that does not include any possibility; some of them are extremely mubham but can be understood with detailed research or kharijiin talmih. Therefore, alkalam alalhi contains kalima with clear maenaa such as nass, zahir, mufassar and muhqam as well as kalima with closed maenaa like mujmal, khafi, mushqil, mutashabih and etc. For this reason, the scholars devoted a large part of their time to kalima-maenaa relationship in order to determine the maenaa of kalima whose maenaa are closed. Thus, scholars have made great efforts for alkalam alalhi to be understood correctly so that people can maintain their lives in accordance with almashiyat al'iilhia. In this context, scholars of fiqh usool (method) have determined a number of alqawaeid in order to prevent mistakes that may occur in the interpretation of na, and for the na to be commented in compliance with almashiyat al'iilhia. Accordingly, the scholars have striven to determine the scope and boundaries of the ta'wil activity. One of these ulema is Al-Juwayni. Ta'wil is the way of interpreting a kalmia (word) to another maenaa (meaning) different from its obvious one, based on a dalil(evidence). In the activity of ta'wil, when there is no dalil supporting the attribution of the kalima to the marjuh and secondary maenaa, the kalima is accepted with zahiri maenaa. However, if there is a dalil, the kalima is attributed to the secondary meaning based on the dalil. First period fiqh and usool ulema actively used ta'wil to determine the maenaa and maqasid meant in the na. However, it is seen that Juwayni was the first person to handle ta'wil as an independent title in the discipline of usool. Juwayni defines ta'wil including the sahih and fasid ta'wil types as follows: "Ta'wil is the attribution of the zahiri kalima to the place of its destination according to the claim of the person making the ta'wil." Juwayni states that ta'wil is not a requirement of the nature of the kalima and jumla (sentence) with the expression "according to the claim of the person making the ta'wil"and that it is the activity of the person making the ta'wil. With the expression "zahiri kalima" he aims to exclude kalima such as na, mufassar, mujmal and mushtaraq from this definition. While Juwayni does not mention talmih in the aforementioned definition, in many parts of his work named Al-Burhan he expresses that it is necessary to support a ta'wil with a dalil and that a ta'wil not supported by dalil is invalid. Juwayni states that all madhhabs (religious schools) act in accordance with ta'wil, that there is no ikhtilaf on this matter, but that the current ikhtilaf is also in details. In order for the ta'wil to be made, Juwayni sets some conditions such as the na 's being open to ta'wil, suitability of the kalima whose ta'wil will be made for the maenaa to be interpreted, in terms of language or custom, the ta'wil's being based on dalil, and the condition that the dalil required in the ta'wil is clearer than the zahir. Since all kalima are not suitable for ta'wil, Juwayni categorized them in terms of their suitability with ta'wil. While some usulists express their opinion that ta'wil can be practised on kalima described as na, Juwayni states that ta'wil is out of question in na because to him, na are kalima with clear maenaa and do not require any ta'wil. Juwayni states that in addition to na, ta'wil cannot be made on mufassar, mujmal and mushtaraq kalima, either. He also emphasizes that ta'wil is in question for the zahir which is understood from the mantuq and the mafhoum of the kalima. He does not deal with the distinction between fasid and batil in ta'wil under a separate title; on the other hand, he puts forward this distinction through examples. Juwayni states that when there is taarudh intibah between two na, not ta'wil but tarjih will be made, but in cases where tarjih is not possible, hesitation will be practised. In this respect, tarjih will be made when the thubut of one of the adilla is zanni and the other is qat'i or when there is an element of tarjih in the nusus such as naskh, bayan, takhsis and tabdeel. However, if there is no element of tarjih, hesitation will be followed. There is no change in Juwayni's understanding of usul al-ta'wil. He accepts the ta'wil of the zahir kalima in the fiqhi and usuli issues. However, it is seen that there is a difference in Juwayni `s understanding of ta'wil in issues of kalam. While in the first periods he said that ta'wil can be made in the khabari attributes, he later states that ta'wil is out of question in khabari attributes.
Keywords: Islamic jurisprudence; Usul; Ta'wil; Muawwal; al-Juwayni